Perineal reconstruction with V-Y advancement flap at the general hospital of Mexico: a case report - Lara Lopez, Rodolfo Luciano Rios; Araujo Azcue, Arsenio Fernando; Silva, Jorge Luis Leal; Gutierrez Rubio, Karla Fabiola Grau (International Journal of Research in Medical Sciences, 2024)
Extramammary Paget's disease represents a rare entity whose only definitive management is resection, resulting in significant raw areas requiring reconstruction by the plastic surgeon. Currently, bilateral gluteal advancement VY fasciocutaneous flaps have been for some time one of the best options for perineal reconstruction, allowing for adequate coverage, low morbidity at the donor site, and satisfactory aesthetic and functional outcomes. In this study, we report the performance of a bilateral VY advancement flap for perineal reconstruction in the Plastic and Reconstructive Surgery Department of the General Hospital of Mexico.